Effect of microalloying with titanium on microstructure and mechanical properties of AZ91 magnesium alloy. (October 2014) - Yu, Z.; Tang, A.; Zhang, L.; Pan, F.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present investigation, the influence of minor Ti addition on the microstructure and mechanical properties of as cast AZ91 magnesium alloy was investigated. The results indicated that the microstructure of the AZ91 alloy with 0·4 wt-% Ti was mainly composed of α-Mg matrix and β-Mg17Al12 eutectic phases. After the addition of 0·4 wt-% Ti to the AZ91 alloy, the average grain size was obviously decreased and the microstructure was drastically refined. The morphology of the β-Mg17Al12 phases was mainly changed from the original partially divorced eutectics to the fully divorced eutectics. A significant enhancement of the tensile properties was found because of titanium addition.